Cleaning Methodology of Solar Panels: Present Technology, Pros, Cons and Solutions (Future Directions) - Akriti Garg (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Dust accumulation on photovoltaic (PV) panels reduces efficiency by 2–98%, necessitating effective cleaning strategies. This paper reviews current methodologies—manual, water-based, robotic, electrostatic, coating-based, and bio-inspired systems—evaluating their advantages, limitations, and sustainability. Using the Preference Selection Index (PSI) approach, waterless methods like electrostatic and coating-based cleaning rank highly for arid regions (Obeidat, 2020). However, high costs, maintenance complexity, and limited empirical data hinder scalability. Emerging IoT-integrated smart systems and machine learning (ML) for predictive maintenance show promise but require validation. Future directions include durable coatings, cost-effective automation and standardized metrics to enhance PV performance. This study provides a roadmap for optimizing cleaning strategies, addressing environmental and economic challenges in solar energy production.